2015
DOI: 10.1007/s10897-015-9822-z
|View full text |Cite
|
Sign up to set email alerts
|

Do Attachment Style and Emotion Regulation Strategies Indicate Distress in Predictive Testing?

Abstract: Predictive genetic testing for a neurogenetic disorder evokes strong emotions, and may lead to distress. The aim of this study is to investigate whether attachment style and emotion regulation strategies are associated with distress in persons who present for predictive testing for a neurogenetic disorder, and whether these psychological traits predict distress after receiving test results. Self-report scales were used to assess attachment insecurity (anxiety and avoidance) and maladaptive emotion regulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…With regard to other predictive tests, factors that have been associated with maladaptive psychological reactions to negative test results are high levels of depression, anxiety, catastrophizing, neuroticism, or hopelessness about one’s health. 2628 Because individuals at risk for schizophrenia are more likely than the general population to experience depression, anxiety, and high rates of neuroticism, it could be that negative psychological reactions to receiving information involving a high risk would be more common in this population. 29,30 In contrast, high levels of ego-strength are associated with psychological well-being 1 year after testing positive for Huntington’s disease, and thus they may act as a protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other predictive tests, factors that have been associated with maladaptive psychological reactions to negative test results are high levels of depression, anxiety, catastrophizing, neuroticism, or hopelessness about one’s health. 2628 Because individuals at risk for schizophrenia are more likely than the general population to experience depression, anxiety, and high rates of neuroticism, it could be that negative psychological reactions to receiving information involving a high risk would be more common in this population. 29,30 In contrast, high levels of ego-strength are associated with psychological well-being 1 year after testing positive for Huntington’s disease, and thus they may act as a protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…These trait variables inherently influence psychological well-being. Therefore, distress is not only influenced by gene status but also by gender, illness history, demographic, or psychological variables (Croyle et al 1997;Cukier et al 2013;van der Meer et al 2015). Tercyak et al also showed that the distress level after receiving a genetic test result also depends on the coping style and not just on the positive or negative gene status (Tercyak et al 2001).…”
Section: Findings Are Contradictorymentioning
confidence: 99%
“…Therefore, distress is not only influenced by gene status but also by gender, illness history, demographic, or psychological variables (Croyle et al 1997;Cukier et al 2013;van der Meer et al 2015). Tercyak et al also showed that the distress level after receiving a genetic test result also depends on the coping style and not just on the positive or negative gene status (Tercyak et al 2001). However, the experience of a prior cancer diagnosis can enhance the coping abilities of mutation carriers (Hallowell et al 2004;Meiser 2005).…”
Section: Findings Are Contradictorymentioning
confidence: 99%
See 1 more Smart Citation
“…Facing an unknown future was scarier than facing a known disease. van der Meer et al (2015) found that attachment anxiety and maladaptive emotional coping such as catastophizing are predictive of pre-and post-test emotional distress. They suggest that positive reappraisal of life with or without the gene mutation can help reduce distress.…”
Section: Discussionmentioning
confidence: 96%